Impact of artificial intelligence on educational actors (2015-2023) - Barrios Tao, Hernando; Díaz-Pérez, Vianney (Revista Colombiana de Ciencias Sociales, 2025)
Introduction: Artificial intelligence systems impact the practices and lives of both students and teachers. Research reviews on artificial intelligence in education have been oriented towards automation, collaboration and use in classroom practices, with a gap in its impact on educational actors. Method: The article, under the PRISMA model, is aimed at interpreting the impacts, in terms of benefits, risks and opportunities of artificial intelligence systems on students and teachers, the main educational actors (2015-2023). The methodology to interpret the texts is analogical hermeneutics, which allows for establishing an analogy between univocal and equivocal visions. Results: Artificial intelligence impacts identity, integral development, relationships, functions, and the very being of educational actors. Conclusions: The voices of educators remain indebted, in relation to the impacts of artificial intelligence on the subjects, of the educational act. It is necessary to strengthen trust, human centrality, and a sapiential integration of these systems in the practices and lives of educational actors.